25.6k views
1 vote
5x + y = -17-3x -3y = 3

1 Answer

1 vote

Given the system of equations:


\begin{gathered} 5x+y=-17\rightarrow(1) \\ -3x-3y=3\rightarrow(2) \end{gathered}

From equation (1), we can find y:


y=-5x-17\rightarrow(3)

Substitute with y from equation (3) into equation (2), then solve to find x


\begin{gathered} -3x-3(-5x-17)=3 \\ -3x+15x+3\cdot17=3 \\ 12x+51=3 \\ 12x=3-51 \\ 12x=-48 \\ \\ x=-(48)/(12)=-4 \end{gathered}

Now, substitute with x into equation (3) to find y


\begin{gathered} y=-5x-17 \\ y=-5\cdot-4-17 \\ y=20-17 \\ \\ y=3 \end{gathered}

The answer is:


\begin{gathered} x=-4,y=3 \\ (x,y)=(-4,3) \end{gathered}

User Isadora
by
5.3k points